Kinetic Modeling of Mammalian Cell Culture Bioprocessing: The Quest to Advance Biomanufacturing. Issue 3 (14th November 2017) - Kyriakopoulos, Sarantos; Ang, Kok Siong; Lakshmanan, Meiyappan; Huang, Zhuangrong; Yoon, Seongkyu; Gunawan, Rudiyanto; Lee, Dong‐Yup
Abstract : Kinetic modeling is the most suitable framework to describe the dynamic behavior of mammalian cell culture although its industrial application is still in its infancy. Herein, the authors reviewed mammalian bioprocess relevant kinetic models, and found that the simple unstructured‐unsegregated approach utilizing empirical Monod‐type kinetics based on limiting substrates and inhibitory metabolites is commonly used due to its traceability and simple formalism. Notably, the available kinetic models are typically small to moderate in size, and the development of large‐scale models is severely hampered by the scarcity of kinetic data and limitations in current parameter estimation methods. The recent availability of abundant high‐throughput multi‐omics datasets from mammalian cell cultures have now paved the way to improve parameterization of kinetic models, and integrate regulatory, signaling, and product quality related intracellular events, as well as cellular metabolism within the modeling framework. Ultimately, the authors foresee that multi‐scale modeling is the way forward in building predictive kinetic models of mammalian cell culture to advance biomanufacturing. Abstract : The mammalian bioprocess relevant kinetic models are reviewed, and their impact and usefulness are analyzed. The integration of multi‐omics data within the modeling framework, and development of multi‐scale models for describing several intracellular processes are current research directions. Particularly, multi‐scale models have great potential to mechanistically link critical process parameters with critical quality attributes, thereby advancing biomanufacturing in the future.